Exploring temporal patterning of psychological skills usage during the week leading up to competition: Lessons for developing intervention programmes. - John Elvis Hagan; Dietmar Pollmann; Thomas Schack (PLoS ONE)
Background and purpose Although sport psychology literature focuses on psychological skills use to promote proficiency, it is still puzzling that current research has focused on psychological skills use only during competition. There remains a scarcity of empirical evidence to support the timing, and content of psychological skill application during the time preceding competition. This study examined the extent to which psychological skills usage are dynamic or stable over a 7-day pre-competitive period and whether any natural learning experiences might have accounted for the acquisition of these skills across gender and skill level. Methods and results Ninety elite and sub-elite table tennis players completed the Test of Performance Strategies (TOPS) at three different periods (7 days, 2 days, 1 hour) before competition. A MANOVA repeated measures with follow-up analyses revealed significant multivariate main effects for only skill level and time-to-competition with no interactions. Specifically, elite (international) athletes reported more usage than sub-elite (national) counterparts for self-talk, imagery and relaxation respectively. Time-to-competition effects showed imagery use decreased steadily across the three time points while reported usage of relaxation were almost at the same level on two time points (7 days and 1 hour) but decreased 2 days before competition. Conclusions Findings suggest an implementation of formalized and periodized psychological skills training programs over continuous training cycles. This may foster a positive long-term athletes' psychological state prior to the onset of competition.